Mystery Shopping as a Strategic Management Practice in Multi-Site Firms - Sidney T. Block; Guido Friebel; Matthias Heinz; Nick Zubanov (Institute of Labor Economics (IZA), 2022)
Anonymous and unannounced site inspections known as "Mystery Shopping" (MS) are common in multi-site service firms, but little is known about the strategic importance of this practice. We conceptualize MS as a monitoring tool firms use to implement the optimal allocation of site resources between sales- and service-related activities in the presence of cross-site reputation spillovers, which is to maximize sales while maintaining service standards. Consistent with this view, data from three retail chains reveal (i) low variation in MS scores, (ii) little correlation of MS scores with sales, and iii) high correlation of sites' MS scores with the likelihood of their supervisors receiving incentive bonuses. Our findings are robust to different estimation specifications, and shed new light on a ubiquitous yet little-studied management practice.
Keywords: L10; M31; M41; M52; 330; mystery shopping; monitoring; reputation spillovers; incentives; service standards